Gut microbiota and its metabolites – molecular mechanisms and management strategies in diabetic kidney disease - Mao, Zi-Hui; Gao, Zhong-Xiuzi; Liu, Dong-Wei; Liu, Zhang-Suo; Wu, Peng (Frontiers in Immunology, 2023)
Diabetic kidney disease (DKD) is one of the major microvascular complications of diabetes mellitus and is also one of the serious risk factors in cardiovascular events, end-stage renal disease, and mortality. DKD is associated with the diversified, compositional, and functional alterations of gut microbiota. The interaction between gut microbiota and host is mainly achieved through metabolites, which are small molecules produced by microbial metabolism from exogenous dietary substrates and endogenous host compounds. The gut microbiota plays a critical role in the pathogenesis of DKD by producing multitudinous metabolites. Nevertheless, detailed mechanisms of gut microbiota and its metabolites involved in the occurrence and development of DKD have not been completely elucidated. This review summarizes the specific classes of gut microbiota-derived metabolites, aims to explore the molecular mechanisms of gut microbiota in DKD pathophysiology and progression, recognizes biomarkers for the screening, diagnosis, and prognosis of DKD, as well as provides novel therapeutic strategies for DKD.